Seeking campus justice:Challenging the ‘criminal justice drift’ in United Kingdom university responses to student sexual violence and misconduct - Cowan, Sharon (2021)
In recent years, growing concerns have been expressed – including in the press and social media – over the apparently inadequate responses of many United Kingdom (UK) universities to complaints of student sexual violence and misconduct (SSVM). In this article, we underscore universities’ legal, ethical, and civic responsibilities to students, which require them to implement effective regimes for the prevention and sanctioning of such behaviour. We suggest, however, that current responses are moving in the wrong direction. More specifically, universities are too often turning (back) towards adversarial and procedural paradigms, developed within the criminal justice system, where the persistence of a ‘justice gap’ in cases of rape and sexual assault has been well documented. We argue that this ‘criminal justice drift’ may frustrate the possibility for more tailored, transformative, and trauma-informed processes for addressing SSVM within higher education institutions